A pragmatic analysis of deictic expressions in economic news articles of the Jakarta Post - Dinda Nadia Dwi Agustin Santoso Putri Putri; Dona Rahayu Sugiharti (Fakultas Ilmu Budaya Universitas 17 Agustus 1945 Surabaya, 2026)
Deixis is a pragmatic device that anchors linguistic expressions to the context in which they are produced, including the participants, time, and place of an utterance. This study investigates deictic expressions in economic news articles published by The Jakarta Post, an English-language digital newspaper widely read in Indonesia. The study aims to identify the context in which deictic expressions occur and to determine the dominant type of deixis used. Employing a descriptive qualitative design with documentation as the data collection technique, seven economic articles published in 2026 were analysed using George Yule's (1996) framework of person, temporal, and spatial deixis. Following Yule's (1996) criterion, an expression was counted as deictic only when its meaning depended on the context of utterance; proper nouns, institutional noun phrases, and grammatically empty pronouns were treated as fixed naming and excluded from the count. The analysis identified 114 deictic instances in total. Temporal deixis was the most dominant type, with 75 instances (65.8%), followed by person deixis with 36 instances (31.6%), while spatial deixis was marginal, with only 3 instances (2.6%). The dominance of temporal deixis reflects the inherently time-bound nature of economic reporting, in which figures, forecasts, and policy statements are only meaningful once anchored to a specific moment or period. These findings diverge from earlier studies on deixis in The Jakarta Post, which generally reported person deixis as dominant, suggesting that deictic distribution is sensitive to genre and to how strictly deixis is operationalised.